2021
DOI: 10.1021/jacs.1c00605
|View full text |Cite
|
Sign up to set email alerts
|

Chemical-Pressure-Modulated BaTiO3 Thin Films with Large Spontaneous Polarization and High Curie Temperature

Abstract: Although BaTiO3 is one of the most famous lead-free piezomaterials, it suffers from small spontaneous and low Curie temperature. Chemical pressure, as a mild way to modulate the structures and properties of materials by element doping, has been utilized to enhance the ferroelectricity of BaTiO3 but is not efficient enough. Here, we report a promoted chemical pressure route to prepare high-performance BaTiO3 films, achieving the highest remanent polarization, P r (100 μC/cm2), to date and high Curie temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 45 publications
1
40
0
Order By: Relevance
“…Since the nature of chemical pressure can also be considered as elastic lattice strain, in a chemical way instead of a physical one, we can describe chemical pressure by applying Eq. (1-2): 54 𝑑𝑃 = −𝐸 𝑑𝑥 𝑥 0…”
Section: Measure Of Chemical Pressurementioning
confidence: 99%
See 2 more Smart Citations
“…Since the nature of chemical pressure can also be considered as elastic lattice strain, in a chemical way instead of a physical one, we can describe chemical pressure by applying Eq. (1-2): 54 𝑑𝑃 = −𝐸 𝑑𝑥 𝑥 0…”
Section: Measure Of Chemical Pressurementioning
confidence: 99%
“…The "interphase strain" method can also be extended to other materials (111). 54 For BaTiO3/BaO, the negative chemical pressure (~ -5.7 GPa) was imposed by the coherent lattice strain from large cubic BaO to small tetragonal BaTiO3, generating high tetragonality (c/a = 1.12) and facilitating large displacements of Ti. This leads to the record remanent polarization Pr (100 μC/cm 2 ) in any forms of BaTiO3 to date with a high Curie temperature Tc (above 1000 °C), see Fig.…”
Section: Negative Thermal Expansion (Nte) In Open-frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of the powder X‐ray diffraction (XRD) patterns in Figure 3b showed that both undoped and doped BaTiO 3 belonged to a tetragonal phase of the space group P 4 mm (99). [ 42 ] The half‐peak widths for the XRD lines were slightly wider for BaTiO 3 :Nb/C and BaTiO 3 :Nb than for BaTiO 3 (Figure S4 , Supporting Information). The tetragonal (101)/(110) diffraction peaks of BaTiO 3 :Nb/C and BaTiO 3 :Nb shifted to higher angles (about 0.12° shifts) when compared to pristine BaTiO 3 (Figure S4 , Supporting Information) as a result of Nb 5+/4+ (0.064/0.068 nm) replacing in part larger Ba 2+ (0.135 nm), according to the analysis using the Bragg equatio, 2 d sin θ = λ .…”
Section: Resultsmentioning
confidence: 99%
“…62 Similar structures were also obtained in BaTiO 3 :BaO epitaxial composite films (c-BTO). 77 The cross-sectional HAADF-STEM image (Fig. 3d) of c-BTO shows that BaTiO 3 and BaO have a coherent interface and that interphase strain exists between them.…”
Section: Performance Optimizationmentioning
confidence: 95%